Simulation of Severe Accident Scenarios in Nuclear Containments. (2017) - Cervenka, Jan; Janda, Zdenek; Jendele, Libor; Pukl, Radomir; Cervenka, Vladimir
Abstract: The paper presents the main theoretical backgrounds and application of FE program ATENA to simulation of severe accident in nuclear structures. The software was developed by Cervenka Consulting, Prague, Czech Republic with the aim to offer a tool for numerical simulation of concrete structures subjected to actions in service, ultimate as well as extreme limit states due to mechanical as well as physical effects. Nonlinear behavior of concrete is modeled by theories of damage and plastic flow [1]. Paper outlines the basic features of the used material model. It demonstrates the model accuracy on results from recent blind prediction competitions [2]. In the last section, it shows examples of simulations of severe accidents scenarios in nuclear power plants structures [4].